Exploring the nuances in the relationship “culture-strategy” for the business world - Kiril Dimitrov (Vanguard Scientific Instruments in Management, 2016)
The current article explores interesting, significant and recently identified nuances in the relationship “culture-strategy”. The shared views of leading scholars at the University of National and World Economy in relation with the essence, direction, structure, role and hierarchy of “culture-strategy” relation are defined as a starting point of the analysis. The research emphasis is directed on recent developments in interpreting the observed realizations of the aforementioned link among the community of international scholars and consultants, publishing in selected electronic scientific databases. In this way a contemporary notion of the nature of “culture-strategy” relationship for the entities from the world of business is outlined.
Keywords: L1; M14; L26; 330; Strategic management; strategy; organization culture; entrepreneurship